1956
DOI: 10.1099/00221287-15-1-106
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Amino Acid Biogenesis: the Synthesis of Alanine from Pyruvate and Ammonia

Abstract: SUMMARY:Washed suspensions of certain bacteria can synthesize alanine from pyruvate and ammonia. This has been studied in detail in Bacillus subtilis. Several other amino acids can be formed from the corresponding keto-acids, but synthesis was most rapid in the case of alanine. Notably, glutamic acid is formed from ketoglutarate relatively slowly, whilst oxalacetate fails to give aspartate. Pyruvate can accept an amino group from a number of amino acids by transamination (but aspartic and glutamic acids are le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1957
1957
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…BacilZus subtilis 4 (Fairhurst et al 1956), maintained on nutrient agar slopes, was used throughout.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…BacilZus subtilis 4 (Fairhurst et al 1956), maintained on nutrient agar slopes, was used throughout.…”
Section: Methodsmentioning
confidence: 99%
“…1~ total phosphate. Choice of incubation time was important since Fairhurst et al (1956) found that reductive amination activity decreased very sharply towards the end of the logarithmic phase of growth. The use of a constant incubation-time with different media giving rise to different rates of growth might therefore produce changes in enzyme activity arising solely from differences in the ' physiological age' of the cultures when harvested.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When leucine and valine are formed from the analogous keto acids, only the L-isomer is found. Since B. subtilis has a racemase active for alanine but not for valine or leucine, it is possible that the L-alanine may be the primary product and which is then racemized.Suspensions of Bacillus subtilis and of some other organisms can synthesize certain amino acids from ammonia and the corresponding keto-acids (Fairhurst, King & Sewell, 1956). When alanine is formed from pyruvate by B. subtilis, the racemic DL-mixture is produced.…”
mentioning
confidence: 99%